Patogenesa Dan Pemilihan Terapi Hemorrhoid - Taufik Sudirman (Medicinus, 2018)
Therapy of hemorrhoids ranges from dietary and lifestyle modification to  surgery, depending on degree and severity of symtoms. While debate continues as to which is the best surgical method for the therapy of hemorrhoids, none of the currently available surgical methods approach the ideal surgical option, which is one that effective while being safe and painless. In reality, the less painful the procedure, the more likely it is to be associated with recurrence post-op. A fuller understanding of the pathophysiology will help to make choices.Keywords: hemorrhoids, pathophysiology, therapy.